PRO KONTRA TERHADAP PROSEDUR DAN SUBSTANSIOMNIBUS LAW RANCANGAN UNDANG-UNDANGCIPTA KERJA - Sadono, Bambang; Rahmiaji, Lintang Ratri (Jurnal Hukum & Pembangunan, 2021)
There are at least two main issues concerning the pros and cons of this omnibus law. First is the posedural issue in the process of making laws. Omnibus law should not be solely to support economic growth and facilitate investment. At thesame time other issues must be considered, for example human rights. So that the omnibus law is not merely a technical problem of legal drafting, but is also part of the implementation of the countrys legal politics. This study uses a literature reviewanalysis method. The results of the deepening of the literatureexplain that the reasons for urgent needs, and limited time, the government or the Parliament can not only pursue the efficiency of time and effectiveness of the target, because the making ofthe law must meet the required procedures, so that the authority granted by the constitution is validated. What must be guarded is not to get the idea of finding a breakthrough, not only concerning the substance of the legislation, but also the draftingprocedures, and the systematic system of the legislation, it will cause new complications in the legislative draftingsystem.